Deferiprone Reduces Hemosiderin Deposits in the Brain of a Patient with Superficial Siderosis - Levy, M. (AJNR Am J Neuroradiol, 2011)
A man with superficial siderosis showed improvement in symptoms and reduction in hemosiderin by MR imaging following treatment with deferiprone, a lipid-soluble iron chelator.